Isolasi Dan Identifikasi Staphylococcus aureus Pada Susu Anjing Di Wilayah Yogyakarta - Guntari Titik Mulyani; Andriani Dwi Hapsari; Soedarmanto Indarjulianto; Tri Untari; Yanuartono .; Slamet Raharjo; Hary Purnamaningsih (Jurnal Sain Veteriner, 2008)
.